(untitled) (Proceedings of Faculty of Civil Engineering, 2022)
This paper describes the basic properties and characteristics of viscosity and presents the most common instruments and methods for determining the dynamic and kinematic viscosity coefficients. Using a viscometer with a falling steel ball of different diameters and masses, in the hydrotechnical laboratory of the Faculty of Civil Engineering in Rijeka a laboratory determination of dynamic and kinematic viscosity coefficient was performed on physical model of 4 different types of liquids (drinking water, seawater, sunflower oil and milk) depending on the change in temperature.